2014
DOI: 10.1093/infdis/jiu235
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Promotes Epithelial Barrier Dysfunction and Intestinal Inflammation

Abstract: This study demonstrates that vitamin D is an important mediator of intestinal epithelial defenses against infectious agents. Vitamin D deficiency predisposes to more-severe intestinal injury in an infectious model of colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(143 citation statements)
references
References 47 publications
11
126
0
6
Order By: Relevance
“…And also recently it is found that caspase-14 deficiency is prone to develop psoriasis in mouse model study [31]. The defective skin barrier may impact the host microbial homeostasis through vitamin D or VDR which involves appropriate immune regulation [32] [33]. In our study, we used two different methods to measure the skin barrier of IMQ-induced psoriasis-like dermatitis on mice and the results indicate that the defective skin barrier including inside-out and outside-in barrier function is involved in the development of psoriasis in mice.…”
Section: Discussionmentioning
confidence: 98%
“…And also recently it is found that caspase-14 deficiency is prone to develop psoriasis in mouse model study [31]. The defective skin barrier may impact the host microbial homeostasis through vitamin D or VDR which involves appropriate immune regulation [32] [33]. In our study, we used two different methods to measure the skin barrier of IMQ-induced psoriasis-like dermatitis on mice and the results indicate that the defective skin barrier including inside-out and outside-in barrier function is involved in the development of psoriasis in mice.…”
Section: Discussionmentioning
confidence: 98%
“…VDR-KO mice were slower to clear Salmonella and Listeria monocytogenes than wild-type (WT) mice (15,16). Feeding mice a vitamin D-deficient diet was associated with increased barrier dysfunction, dysbiosis of the microbiota, and more intestinal inflammation following Citrobacter rodentium infection (17), whereas administration of 1,25(OH) 2 D decreased the Th17 response and increased C. rodentium shedding on day 10 postinfection (18). Dietary vitamin D treatment in mice was beneficial for resolving inflammation but did not alter their M. tuberculosis bacterial burdens (19).…”
Section: Vitamin D and The Immune Systemmentioning
confidence: 99%
“…Coerentemente, verificou-se que camundongos deficientes desta vitamina eram ineficientes em atenuar os efeitos inflamatórios de LPS, endotoxina presente em bactérias gram-negativas (RYZ et al, 2015). Embora não seja claro o papel das diferentes bactérias que habitam o trato gastrointestinal, sabe-se que estas podem participar da fisiopatologia de doenças autoimunes e inflamatórias, apontando um caminho para o entendimento da relação da deficiência de uma substância imunomoduladora exacerbada (CANTAREL et al, 2015;CANTORNA et al, 2014 Frente às constatações de que a combinação de baixas concentrações de vitamina D e certos padrões de microbiota poderia ser deletéria para a barreira intestinal, aprofundou-se na investigação sobre mecanismos pelos quais tal vitamina contribuiria para mantê-la saudável (FROICU & CANTORNA, 2007;KONG et al, 2008;ZHAO et al, 2012;ASSA et al, 2014 (BASHIR et al, 2015). Dessa forma, levanta-se a expectativa de que a suplementação desta vitamina possa ser útil na prevenção e/ou tratamento de diversas doenças em decorrência de efeitos benéficos sobre a microbiota intestinal (SZODORAY et al, 2008).…”
Section: As Bactérias Mais Abundantes Na Microbiota Intestinal Pertenunclassified
“…Por outro lado, parece que as concentrações de 1,25(OH)2D3 e o VDR regulariam a inflamação e a microbiota para garantir a homeostase no trato gastrointestinal (OOI et al, 2013;ASSA et al, 2014;CANTORNA et al, 2014;RAFTERY et al, 2015;CANTORNA, 2016).…”
Section:  Doença Inflamatória Intestinalunclassified
See 1 more Smart Citation